Lateral Indentation of a Thin Elastic Film - Hamm-Hahn, L; Cerda-Villablanca, E (Royal Society of Chemistry, 2022)
Indentation is a standard, widely used technique in mechanical assays and theoretical analysis. It unveils the fundamental modes of deformation and predicts the response of the material under more complex loads. Here we present an experimental setup for testing thin-film materials by studying the lateral indentation of a narrow opening cut into a film, triggering a cascade of buckling events. The force response F is dominated by bending and stretching effects for small displacements and slowly varies with indenter displacement F ∼ d2/5, to finally reach a wrinkled state that results in a robust nonlinear asymptotic relation, F ∼ d4. Experiments with films of various thicknesses and material properties, and numerical simulations confirm our analysis and help to define an order parameter that accounts for the different response regimes observed in experiments and simulations. This journal is © The Royal Society of Chemistry.